Solving by Quadratic Formula

I know the formula but I this problem seems to be wrong when I solve it.

m^2+5m-6=0

a=m

b=5

c=-6

x=-5+-√5^2-4(M)(-6) over 2(M)

So I get -5+-√25-24/2

-5+-√1/2

-5+1/2=-2 or -5-1/2=-3

That is what I got however the answer is suppose to be -6 and 1... Just wondering where I went wrong.

Re: Solving by Quadratic Formula

Quote:

Originally Posted by

**Past45** I know the formula but I this problem seems to be wrong when I solve it.

m^2+5m-6=0

a=m

b=5

c=-6

x=-5+-√5^2-4(M)(-6) over 2(M)

So I get -5+-√25-24/2

-5+-√1/2

-5+1/2=-2 or -5-1/2=-3

That is what I got however the answer is suppose to be -6 and 1... Just wondering where I went wrong.

a is the number that the square term is multiplied by. In this case, a = 1, not m.

Re: Solving by Quadratic Formula

Right, but it it still is going to have those same numbers when you solve them.

Re: Solving by Quadratic Formula

$\displaystyle m^2+5m-6=0$

$\displaystyle m = \frac{-5 \pm \sqrt{5^2 - 4(1)(-6)}}{2}$

try again ... pay close attention to your **signs**

Re: Solving by Quadratic Formula